2010
DOI: 10.1016/j.bbamcr.2009.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Statin-triggered cell death in primary human lung mesenchymal cells involves p53-PUMA and release of Smac and Omi but not cytochrome c

Abstract: Statins inhibit 3-hydroxy-3-methyl-glutarylcoenzyme CoA (HMG-CoA) reductase, the proximal enzyme for cholesterol biosynthesis. They exhibit pleiotropic effects and are linked to health benefits for diseases including cancer and lung disease. Understanding their mechanism of action could point to new therapies, thus we investigated the response of primary cultured human airway mesenchymal cells, which play an effector role in asthma and chronic obstructive lung disease (COPD), to simvastatin exposure. Simvastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(111 citation statements)
references
References 72 publications
9
101
1
Order By: Relevance
“…ASM cells undergo apoptosis under various conditions, and a decreased rate of apoptosis has been reported to contribute to excessive ASM mass in asthma (21). Recent studies demonstrated that statins inhibit ASM growth by inducing apoptosis of ASM cells (17). Effects of TAS2R agonists on ASM mass could also be the result of cytotoxicity or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…ASM cells undergo apoptosis under various conditions, and a decreased rate of apoptosis has been reported to contribute to excessive ASM mass in asthma (21). Recent studies demonstrated that statins inhibit ASM growth by inducing apoptosis of ASM cells (17). Effects of TAS2R agonists on ASM mass could also be the result of cytotoxicity or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…12663). The plasmid was transfected into HEK293T cells using a Ca 2+ -phosphate three-plasmid transfection VSVG (envelope vector), 8.2vpr (packaging vector) and expression vector for -dystroglycan to generate lentivirus by counting the puromycin-resistant colonies, as previously described (Ghavami et al, 2010;Kung et al, 2000). A non-coding -dystroglycan refractory shRNA (shRNAi noncode) was used as a transduction control.…”
Section: -Dystroglycan Rnaimentioning
confidence: 99%
“…Cytosolic and membrane fractions were generated using a subcellular fractionation technique at 4°C as previously described (Ghavami et al, 2010). Cells were scraped in ice-cold buffer (10 mM Tris-HCl, pH 7.5, 0.1 mM EDTA, 0.1 mM EGTA, 1 mM dithiothreitol, and protease inhibitor cocktail), sonicated on ice three times for 5 seconds, and then the homogenate was separated into cytoplasmic and membrane fractions by ultra-centrifugation (100,000 g for 35 minutes).…”
Section: Subcellular Fractionationmentioning
confidence: 99%
“…For example, treatment of cells with pemetrexed and simvastatin promoted autophagy and inhibited apoptosis (16), while oridonin phosphate induced autophagy and enhanced apoptotic cell death (17). However, the precise mechanisms that determine autophagy, apoptosis, and their interaction remain to be elucidated.A number of studies in tumor cells (e.g., hepatocellular carcinoma and OVCAR-3 cancer cells) have shown that the p53 tumor suppressor protein, which is an important cellular stress sensor, can trigger cell cycle arrest and apoptosis and also regulate autophagy (18)(19)(20). Activation of p53 in response to a death stimulus leads to the transcription of genes involved in apoptosis, including PUMA (p53 upregulated modulator of apoptosis), AMPK (AMPactivated protein kinase), and Bax in the nucleus.…”
mentioning
confidence: 99%